Patterns and determinants of woody encroachment in the eastern Eurasian steppe. (29th March 2021) - Liu, Xu; Feng, Siwen; Liu, Hongyan; Ji, Jue
Abstract: The Eurasian steppe is the largest grassland on Earth, with its eastern part covering northern China, Mongolia, and southern Siberia in Russia. Past and future climate warming has been highlighted by previous works; however, how vegetation cover, particularly woody versus herbaceous cover, has and will respond remains an open question. Through the fractional woody vegetation cover (FWVC) and fractional herbaceous vegetation cover (FHVC) estimated by the random forest method based on multisource remote sensing images, we report here that a slight woody encroachment has occurred at a rate of 1% /decade, mostly concentrated in the forest‐steppe ecotone at its humid edge since 2000. The woody encroachment was mainly driven by climate warming, especially when it became warmer and wetter, mainly in areas with weakened active fires. At the same time, grass recovery has occurred at the center of this region under slight warming and drying, while human disturbance has shown a more significant influence than the effects of climate warming on this change. Under the assumption that human disturbance remains constant, the woody cover and herbs cover are projected to increase by 2040, while the change of FHVC shows more spatial heterogeneity.